“Бессарабська печатка” - Стецюченко, О. (Чорноморська минувшина, 2009)
Запропонована інформація про знахідку у 2007 р. на території Одеської області особистої печатки кінця ХІХ – початку ХХ ст. Власник печатки мав призвіще “Казак” і воно є центральним написом на печатці, яка ілюструється. In the article there is an information on a find of the personal seal of the end ХІХ – beginning of the ХХ c. made in 2007 in Odesa region. The former owner of the seal had the surname “Cоssack” written in the center of it. The article is followed by illustration of the seal.